SELF REGULATED LEARNING STRATEGIES IN IMPROVING STUDENTS ENGLISH ACHIEVEMENT - Fitriyeni Fitriyeni; Tri Widyastuti (Jurnal Akrab Juara, 2018)
This study aims to find out the correlation between Self-Regulated Learning Strategies (SRLS) and Students’ English Achievement. The knowledge and application of SRLS will significantly influence learners academic achievement due to their autonomously participation and involvement in regulating their own learning. Research methodology used is descriptive quantitative study with 100 participants from grade first high school students, collected using random sampling technique. Data was collected through questionnaires and English proficiency test. The result of this study shows that there is positive correlation between SRLS and Students’ English Achievement. Students who have better knowledge and use SRLS in their study are getting better achievement in English test because of their responsibility in learning. The refore, it is important for teachers to apply SRLS in the teaching and learning process to increase and foster the students’ implementation of SRLS in their learning.